Far Lateral Approach for Clipping of a Posterior Inferior Cerebellar Artery Aneurysm - Basma, Jaafar; Nguyen, Vincent N.; Mangham, William M.; Khan, Nickalus R.; Sorenson, Jeffrey; Michael, L. Madison, II (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objectives To describe a far lateral approach for microsurgical clipping of a ruptured posterior inferior cerebellar artery (PICA) aneurysm involving the hypoglossal nerve, with emphasis on the microsurgical anatomy, and technique.Design A far lateral craniotomy is performed in the lateral decubitus position and the transverse and sigmoid sinuses were exposed. After opening the dura, sutures are placed to allow gentle mobilization of the sinuses. The ipsilateral cerebellar tonsil is mobilized and the PICA is followed to its junction with the vertebral artery. Hypoglossal nerve rootlets are draped over the dome of the aneurysm. Mobilization of the PICA and the hypoglossal nerve away from the lateral medulla allows microsurgical clipping of the aneurysm neck. Photographs of the region are borrowed from Dr Rhoton's laboratory to illustrate the microsurgical anatomy.Participants The senior authors performed the surgery. The video was edited by Drs. V.N. and J.B. Chart review and literature review were performed by Drs. W.M. and J.B.Outcome Measures Outcome was assessed with successful clip occlusion and postoperative neurological function.Results There was complete clip occlusion of the PICA aneurysm with no postoperative neurological deficits. The patient was discharged home after an uneventful hospital course.Conclusion The far lateral approach provides an adequate corridor to the ventrolateral brainstem for microsurgical treatment of PICA aneurysms. An adequate understanding of the relevant microsurgical anatomy is the key to safe and effective clipping in this region.The link to the video can be found at: https://youtu.be/yhjKRIG5H74.
Keywords: aneurysm; PICA; far lateral; craniotomy; skull base; cerebrovascular; microsurgery; clipping